Analysis and application on sensitivity factors of cross validation of fill rate of CPR1000 unit reactor core coolant monitoring system. (November 2019) - Chen, Yongwei; Xie, Yongjing; Wang, Zuo; Luan, Zhenhua; Ling, Jun
Highlights: The mathematical model for reactor core coolant fill rate is built. The sensitivity analysis model adopts the GUM method. Sensitivity factors of cross validation of fill rate are determined. The optimal window and system condition setting for the redundancy cross validation is proposed. Abstract: The coolant fill rate setting of CPR1000 unit reactor core has train A/B of redundancy measuring channels, whose function is to monitor the water inventory of reactor core under the working conditions of water loss and other accidents to ensure the safety of reactor core. In order to confirm the reliability of train A/B of redundancy measuring channels, a technical solution for the cross comparison of fill rate during the reactor refueling cycle is proposed to validate the consistency of train A/B of redundancy measuring and computing channels. Through the cross validation model of fill rate of reactor core coolant monitoring system, the sensitivity analysis on such input variables as relative pressure of primary coolant circuit, temperature of reactor core, differential pressure of reactor core, absolute pressure of containment, etc. shall be conducted. The sensitivity analysis model adopts the GUM method for the law of propagation of uncertainty, through which the proportion of uncertainty components of various input variables can be obtained. Moreover, the aided analysis based on the engineering statistic data from the nuclear power units of various bases shall be conducted to determine the sensitivity variables of cross validation of fill rate. Based on the combination of variable sensitivity analysis and process variables influence analysis with the switching process of the unit uplink status and the objective law of system change, the optimal window and system condition setting for the redundancy cross validation is proposed, including such factors and statuses as system pressure, temperature, running condition of primary pump, etc. Such solution has been applied to engineering sites, and has achieved good effects which can prove its feasibility and effectiveness.